The societal transformation: The role of social networking platforms in shaping the digital age - Clever S. Cagatin (Interdisciplinary Social Studies, 2024)
This study explores the influence of social networking platforms in shaping the digital age and driving societal transformation. It examines how these platforms have revolutionized communication, information sharing, and networking on a global scale. The major finding of this study is that social networking platforms have greatly influenced society by creating new channels of communication, facilitating information-sharing, and fostering online communities. These platforms have enabled individuals to connect with others across distances, share personal experiences, and collaborate on various projects. They have also provided a platform for marginalized groups to voice their opinions and advocate for social change. The study recommends that individuals and organizations should be mindful of the potential risks and challenges associated with social networking platforms. These include issues such as privacy concerns, the spread of misinformation, and the potential for online harassment. It is important for individuals to critically evaluate the information they consume and to actively engage in online conversations that promote constructive dialogue.